Photosynthesis and resource distribution through plant canopies - Niinemets, Uelo (PLANT CELL AND ENVIRONMENT, 2007)
Plant canopies are characterized by dramatic gradients of light between canopy top and bottom, and interactions between light, temperature and water vapour deficits. This review summarizes current knowledge of potentials and limitations of acclimation of foliage photosynthetic capacity (A(max)) and light-harvesting efficiency to complex environmental gradients within the canopies. Acclimation of A(max) to high light availability involves accumulation of rate-limiting photosynthetic proteins per unit leaf area as the result of increases in leaf thickness in broad-leaved species and volume: total area ratio and mesophyll thickness in species with complex geometry of leaf cross-section. Enhancement of light-harvesting efficiency in low light occurs through increased chlorophyll production per unit dry mass, greater leaf area per unit dry mass investment in leaves and shoot architectural modifications that improve leaf exposure and reduce within-shoot shading. All these acclimation responses vary among species, resulting in species-specific use efficiencies of low and high light. In fast-growing canopies and in evergreen species, where foliage developed and acclimated to a certain light environment becomes shaded by newly developing foliage, leaf senescence, age-dependent changes in cell wall characteristics and limited foliage re-acclimation capacity can constrain adjustment of older leaves to modified light availabilities. The review further demonstrates that leaves in different canopy positions respond differently to dynamic fluctuations in light availability and to multiple environmental stresses. Foliage acclimated to high irradiance respond more plastically to rapid changes in leaf light environment, and is more resistant to co-occurring heat and water stress. However, in higher light, co-occurring stresses can more strongly curb the efficiency of foliage photosynthetic machinery through reductions in internal diffusion conductance to CO2. This review demonstrates strong foliage potential for acclimation to within-canopy environmental gradients, but also highlights complex constraints on acclimation and foliage functioning resulting from light x foliage age interactions, multiple environmental stresses, dynamic light fluctuations and species-specific leaf and shoot structural constraints.
Keywords: acclimation kinetics; age effects; foliage aggregation; leaf longevity; leaf structure; light acclimation; nitrogen content; support costs; tocopherol content; xanthophyll cycle

Photosynthesis and resource distribution through plant canopies - Niinemets, Uelo (PLANT CELL AND ENVIRONMENT, 2007)
Plant canopies are characterized by dramatic gradients of light between canopy top and bottom, and interactions between light, temperature and water vapour deficits. This review summarizes current knowledge of potentials and limitations of acclimation of foliage photosynthetic capacity (A(max)) and light-harvesting efficiency to complex environmental gradients within the canopies. Acclimation of A(max) to high light availability involves accumulation of rate-limiting photosynthetic proteins per unit leaf area as the result of increases in leaf thickness in broad-leaved species and volume: total area ratio and mesophyll thickness in species with complex geometry of leaf cross-section. Enhancement of light-harvesting efficiency in low light occurs through increased chlorophyll production per unit dry mass, greater leaf area per unit dry mass investment in leaves and shoot architectural modifications that improve leaf exposure and reduce within-shoot shading. All these acclimation responses vary among species, resulting in species-specific use efficiencies of low and high light. In fast-growing canopies and in evergreen species, where foliage developed and acclimated to a certain light environment becomes shaded by newly developing foliage, leaf senescence, age-dependent changes in cell wall characteristics and limited foliage re-acclimation capacity can constrain adjustment of older leaves to modified light availabilities. The review further demonstrates that leaves in different canopy positions respond differently to dynamic fluctuations in light availability and to multiple environmental stresses. Foliage acclimated to high irradiance respond more plastically to rapid changes in leaf light environment, and is more resistant to co-occurring heat and water stress. However, in higher light, co-occurring stresses can more strongly curb the efficiency of foliage photosynthetic machinery through reductions in internal diffusion conductance to CO2. This review demonstrates strong foliage potential for acclimation to within-canopy environmental gradients, but also highlights complex constraints on acclimation and foliage functioning resulting from light x foliage age interactions, multiple environmental stresses, dynamic light fluctuations and species-specific leaf and shoot structural constraints.
The following values have no corresponding Zotero field: pub-location: 9600 GARSINGTON RD, OXFORD OX4 2DQ, OXON, ENGLAND publisher: BLACKWELL PUBLISHING
Keywords: acclimation kinetics; age effects; foliage aggregation; leaf longevity; leaf structure; light acclimation; nitrogen content; support costs; tocopherol content; xanthophyll cycle

Complex adjustments of photosynthetic potentials and internal diffusion conductance to current and previous light availabilities and leaf age in Mediterranean evergreen species Quercus ilex - NIINEMETS, Ü L O; CESCATTI, ALESSANDRO; RODEGHIERO, MIRCO; TOSENS, TIINA (Plant, Cell & Environment, 2006)
Mature non-senescent leaves of evergreen species become gradually shaded as new foliage develops and canopy expands, but the interactive effects of integrated light during leaf formation (QintG), current light (QintC) and leaf age on foliage photosynthetic competence are poorly understood. In Quercus ilex L., we measured the responses of leaf structural and physiological variables to QintC and QintG for four leaf age classes. Leaf aging resulted in increases in leaf dry mass per unit area (MA), and leaf dry to fresh mass ratio (DF) and decreases in N content per dry mass (NM). N content per area (NA) was independent of age, indicating that decreases in NM reflected dilution of leaf N because of accumulation of dry mass (NA = NM MA). MA, DF and NA scaled positively with irradiance, whereas these age-specific correlations were stronger with leaf growth light than with current leaf light. Area-based maximum ribulose 1,5-bisphosphate carboxylase/oxygenase (Rubisco) carboxylase activity (VcmaxA), capacity for photosynthetic electron transport (JmaxA) and the rate of non-photorespiratory respiration in light (RdA) were also positively associated with irradiance. Differently from leaf structural characteristics, for all data pooled, these relationships were stronger with current light with little differences among leaves of different age. Acclimation to current leaf light environment was achieved by light-dependent partitioning of N in rate-limiting proteins. Mass-based physiological activities decreased with increasing leaf age, reflecting dilution of leaf N and a larger fraction of non-photosynthetic N in older leaves. This resulted in age-dependent modification of leaf photosynthetic potentials versus N relationships. Internal diffusion conductance (gm) per unit area (gmA) increased curvilinearly with increasing irradiance for two youngest leaf age classes and was independent of light for older leaves. In contrast, gm per dry mass (gmM) was negatively associated with light in current-year leaves. Greater photosynthetic potentials and moderate changes in diffusion conductance resulted in greater internal diffusion limitations of photosynthesis in higher light. Both area- and mass-based gm decreased with increasing leaf age. The decrease in diffusion conductance was larger than changes in photosynthetic potentials, leading to larger CO2 drawdown from leaf internal air space to chloroplasts (ΔC) in older leaves. The increases in diffusion limitations in older leaves and at higher light scaled with age- and light-dependent increases in MA and DF. Overall, our study demonstrates a large potential of foliage photosynthetic acclimation to changes in leaf light environment, but also highlights enhanced structural diffusion limitations in older leaves that result from leaf structural acclimation to previous rather than to current light environment and accumulation of structural compounds with leaf age.
Keywords: CO2 drawdown; growth irradiance; leaf age; leaf structure; mesophyll conductance; nitrogen content; photosynthetic capacity

Complex adjustments of photosynthetic potentials and internal diffusion conductance to current and previous light availabilities and leaf age in Mediterranean evergreen species Quercus ilex - NIINEMETS, Ü L. O.; CESCATTI, ALESSANDRO; RODEGHIERO, MIRCO; TOSENS, TIINA (Plant, Cell & Environment, 2006)
Mature non-senescent leaves of evergreen species become gradually shaded as new foliage develops and canopy expands, but the interactive effects of integrated light during leaf formation (QintG), current light (QintC) and leaf age on foliage photosynthetic competence are poorly understood. In Quercus ilex L., we measured the responses of leaf structural and physiological variables to QintC and QintG for four leaf age classes. Leaf aging resulted in increases in leaf dry mass per unit area (MA), and leaf dry to fresh mass ratio (DF) and decreases in N content per dry mass (NM). N content per area (NA) was independent of age, indicating that decreases in NM reflected dilution of leaf N because of accumulation of dry mass (NA = NM MA). MA, DF and NA scaled positively with irradiance, whereas these age-specific correlations were stronger with leaf growth light than with current leaf light. Area-based maximum ribulose 1,5-bisphosphate carboxylase/oxygenase (Rubisco) carboxylase activity (VcmaxA), capacity for photosynthetic electron transport (JmaxA) and the rate of non-photorespiratory respiration in light (RdA) were also positively associated with irradiance. Differently from leaf structural characteristics, for all data pooled, these relationships were stronger with current light with little differences among leaves of different age. Acclimation to current leaf light environment was achieved by light-dependent partitioning of N in rate-limiting proteins. Mass-based physiological activities decreased with increasing leaf age, reflecting dilution of leaf N and a larger fraction of non-photosynthetic N in older leaves. This resulted in age-dependent modification of leaf photosynthetic potentials versus N relationships. Internal diffusion conductance (gm) per unit area (gmA) increased curvilinearly with increasing irradiance for two youngest leaf age classes and was independent of light for older leaves. In contrast, gm per dry mass (gmM) was negatively associated with light in current-year leaves. Greater photosynthetic potentials and moderate changes in diffusion conductance resulted in greater internal diffusion limitations of photosynthesis in higher light. Both area- and mass-based gm decreased with increasing leaf age. The decrease in diffusion conductance was larger than changes in photosynthetic potentials, leading to larger CO2 drawdown from leaf internal air space to chloroplasts (ΔC) in older leaves. The increases in diffusion limitations in older leaves and at higher light scaled with age- and light-dependent increases in MA and DF. Overall, our study demonstrates a large potential of foliage photosynthetic acclimation to changes in leaf light environment, but also highlights enhanced structural diffusion limitations in older leaves that result from leaf structural acclimation to previous rather than to current light environment and accumulation of structural compounds with leaf age.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: CO2 drawdown; growth irradiance; leaf age; leaf structure; mesophyll conductance; nitrogen content; photosynthetic capacity

Influence of increased atmospheric CO2 concentration on quality of plant material and litter decomposition - Coûteaux, Marie-Madeleine; Kurz, Cathy; Bottner, Pierre; Raschi, Antonio (Tree Physiology, 1999)
Nitrogen (N) and lignin concentrations in plant tissues and litter of plants grown in greenhouses or open-top chambers in elevated atmospheric CO2 concentration were compared with those of plants grown in ambient air in short-term studies. We also compared the N concentration of plant material of Quercus ilex L. and Q. pubescens Willd. growing in the vicinity of natural CO2-springs with that of the same species growing at a control site. In the short-term studies, elevated CO2 caused significant decreases in tissue N concentration and the extent of the decrease varied with species. Nitrogen amendment of the soil lessened the CO2-enrichment effect. Lignin concentration was modified by elevated CO2 and the effect was species specific, but no general positive or negative trend was evident. A comparison of trees growing under natural conditions near a natural CO2-spring and at a control site revealed no site differences in N concentration of the plant material. A comparison of published results on decomposition rates of litter produced in elevated atmospheric CO2 and in ambient air indicated that CO2 enrichment can cause both enhancements and decreases of carbon mineralization. We conclude that (1) long-term responses to elevated CO2 could differ from the results obtained from short-term studies and that (2) biodiversity could be an important factor altering the sign of the feedback on atmospheric CO2 concentration. We also discuss the implications of our finding of a long-term, inhibitory effect of the initial N concentration of litter on the decomposition rate of litter and its consequence on ecosystem feedback.
10.1093/treephys/19.4-5.30110.1093/treephys/19.4-5.301
Keywords: Biodiversity; Carbon dioxide; Global change; lignin content; nitrogen content

Influence of increased atmospheric CO2 concentration on quality of plant material and litter decomposition - Coûteaux, Marie-Madeleine; Kurz, Cathy; Bottner, Pierre; Raschi, Antonio (Tree Physiology, 1999)
Nitrogen (N) and lignin concentrations in plant tissues and litter of plants grown in greenhouses or open-top chambers in elevated atmospheric CO2 concentration were compared with those of plants grown in ambient air in short-term studies. We also compared the N concentration of plant material of Quercus ilex L. and Q. pubescens Willd. growing in the vicinity of natural CO2-springs with that of the same species growing at a control site. In the short-term studies, elevated CO2 caused significant decreases in tissue N concentration and the extent of the decrease varied with species. Nitrogen amendment of the soil lessened the CO2-enrichment effect. Lignin concentration was modified by elevated CO2 and the effect was species specific, but no general positive or negative trend was evident. A comparison of trees growing under natural conditions near a natural CO2-spring and at a control site revealed no site differences in N concentration of the plant material. A comparison of published results on decomposition rates of litter produced in elevated atmospheric CO2 and in ambient air indicated that CO2 enrichment can cause both enhancements and decreases of carbon mineralization. We conclude that (1) long-term responses to elevated CO2 could differ from the results obtained from short-term studies and that (2) biodiversity could be an important factor altering the sign of the feedback on atmospheric CO2 concentration. We also discuss the implications of our finding of a long-term, inhibitory effect of the initial N concentration of litter on the decomposition rate of litter and its consequence on ecosystem feedback.
10.1093/treephys/19.4-5.301
Keywords: Biodiversity; Carbon dioxide; Global change; lignin content; nitrogen content

Co-occurrence of trees with different leaf habit: A functional approach on Mediterranean oaks - Damesin, Claire; Rambal, Serge; Joffre, Richard (Acta Oecologica, 1998)
Tree species can be split into two groups in terms of their leaf life-spans: evergreens and deciduous. Their distinct geographical dis- tribution suggests that these two groups have functional characteristics adapted to specific environments. However, deciduous and evergreen trees co-exist in some regions, such as those with a Mediterranean climate. They provide good models for comparing the properties of both trees and obtaining an understanding of how diversity is maintained. This is the case in southern France, where the evergreen holm oak (Quercus ilex) and the deciduous downy oak (Quercus pubescens) co-exist. A research programme has been conducted which compares the functioning of these two species at various scales, with the aim of anticipating their distribution in the event of climatic change. The ‘cost-benefit‘ model of Mooney and Dunn has been tested at leaf scale. Q. pubescens has a lower area-based construction cost than Q. ibex, but does not have a higher photosynthetic capacity. Despite differences in biochemical composition, size and mass per unit area, the leaves of the two species respond similarly to limited water conditions. Furthermore, the carbon isotope composition suggests that they have similar intrinsic water-use efficiencies. At the ecosystem scale, preliminary data are available on water, carbon and nitrogen use: i) measurements of leaf water potentials show that drought constraint starts at the same time and with the same rate and intensity in both species: ii) leaf area index was higher in Q. ilex woodlands; and iii) the release rate of nitrogen from the litter was faster in Q. ilex ecosystems. Together, these results indicate that the key factors distinguishing functions of deciduous and evergreen Quercus are more apparent at the ecosystem level than at the leaf level
Keywords: carbon isotope composition; construction cost; deciduous tree; evergreen tree; leaf area index; leaf gas exchange; Leaf habit; Mediterranean-type climate; nitrogen content; Quercus ilex; Quercus pubescens

Co-occurrence of trees with different leaf habit: A functional approach on Mediterranean oaks - Damesin, Claire; Rambal, Serge; Joffre, Richard (Acta Oecologica, 1998)
Tree species can be split into two groups in terms of their leaf life-spans: evergreens and deciduous. Their distinct geographical dis- tribution suggests that these two groups have functional characteristics adapted to specific environments. However, deciduous and evergreen trees co-exist in some regions, such as those with a Mediterranean climate. They provide good models for comparing the properties of both trees and obtaining an understanding of how diversity is maintained. This is the case in southern France, where the evergreen holm oak (Quercus ilex) and the deciduous downy oak (Quercus pubescens) co-exist. A research programme has been conducted which compares the functioning of these two species at various scales, with the aim of anticipating their distribution in the event of climatic change. The ‘cost-benefit‘ model of Mooney and Dunn has been tested at leaf scale. Q. pubescens has a lower area-based construction cost than Q. ibex, but does not have a higher photosynthetic capacity. Despite differences in biochemical composition, size and mass per unit area, the leaves of the two species respond similarly to limited water conditions. Furthermore, the carbon isotope composition suggests that they have similar intrinsic water-use efficiencies. At the ecosystem scale, preliminary data are available on water, carbon and nitrogen use: i) measurements of leaf water potentials show that drought constraint starts at the same time and with the same rate and intensity in both species: ii) leaf area index was higher in Q. ilex woodlands; and iii) the release rate of nitrogen from the litter was faster in Q. ilex ecosystems. Together, these results indicate that the key factors distinguishing functions of deciduous and evergreen Quercus are more apparent at the ecosystem level than at the leaf level
Keywords: carbon isotope composition; construction cost; deciduous tree; evergreen tree; leaf area index; leaf gas exchange; Leaf habit; Mediterranean-type climate; nitrogen content; Quercus ilex; Quercus pubescens